1990
DOI: 10.1136/thx.45.3.170
|View full text |Cite
|
Sign up to set email alerts
|

Case-control study of prescribed fenoterol and death from asthma in New Zealand, 1977-81.

Abstract: A previous New Zealand case-control study of asthma deaths in the 5-45 year age group during 1981-3 found that prescription of fenoterol (by metered dose inhaler) was associated with an increased risk of death in patients with severe asthma. One major criticism of this study was that drug data for the cases and controls came from different sources. A new case-control design has been used to evaluate the same hypothesis, with a different set of asthma deaths, the same source for drug information being used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
103
0
3

Year Published

1990
1990
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(114 citation statements)
references
References 19 publications
8
103
0
3
Order By: Relevance
“…Many investigations were conducted to elucidate uncertainty about the confounding between severity and fenoterol use [4][5][6][7][8][9][10][11] Opinion is still divided: one is that fenoterol was not associated with severe life-threatening attacks (LTA) after controlling severity 8,10);and the other is that the association between fenoterol and asthma death was significant, but after adjustment for markers of asthma severity was made, there was no difference in the magnitude of the association between fenoterol and asthma death 4-7,9,11) In this paper, we report the results of a case-control study on prescribed drug therapy, severity, and the risk of death from asthma and LTA in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations were conducted to elucidate uncertainty about the confounding between severity and fenoterol use [4][5][6][7][8][9][10][11] Opinion is still divided: one is that fenoterol was not associated with severe life-threatening attacks (LTA) after controlling severity 8,10);and the other is that the association between fenoterol and asthma death was significant, but after adjustment for markers of asthma severity was made, there was no difference in the magnitude of the association between fenoterol and asthma death 4-7,9,11) In this paper, we report the results of a case-control study on prescribed drug therapy, severity, and the risk of death from asthma and LTA in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…5) Similar results have also been reported recently for fenoterol MDI. [6][7][8] However, with regard to fenoterol MDI, previous studies showed that this medication did not cause an increase in death from asthma classied according to the severity of patients who were prescribed other b-agonist MDIs. 10) Furthermore, such a relationship has been observed only in Australia.…”
Section: Discussionmentioning
confidence: 96%
“…3,4) Another problem relates to a potentially higher risk of death from asthma posed by some b-agonists due to the patient's dependency on and excess use of these inhalers, which was initially noted with the regular and excessive use of isoprenaline 5) and later with fenoterol. [6][7][8] In this regard, whether fenoterol MDI increases the risk of death from asthma is still controversial. [9][10][11] Accurate conclusions have not been made; however, proper instructions on the inhalation manoeuvres using bagonist MDIs as well as other useful information on self-management by asthmatics are undoubtedly necessary for reducing deaths from asthma and preventing exacerbation of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, no studies have been able to satisfactorily compare and contrast the factors in the patients who have died with those of individuals with severe asthma who have not died. Indeed, this has become a major issue in interpreting the data relating to fenoterol usage in the New Zealand studies of asthma deaths during the 1970s [16][17][18], and a subsequent study from Saskatchewan, Canada [19]. There is much dispute about the selection of appropriate comparator populations and the use of statistical adjustment for confounder factors [18].…”
Section: Discussionmentioning
confidence: 99%